Incidencia del ocio sobre el comportamiento ambiental del reciclaje de residuos sólidos durante la pandemia por COVID-19 en el Ecuador. - Ortega Mendez, Ermita del Cisne (2023)
The COVID-19 pandemic imposed a global health emergency, however, it has created environmental problems arising from waste management. This study emphasises the challenges of large-scale waste disposal during this time and the response practices in Ecuador. Taking as a theoretical basis the postulates of Fishbein & Ajzen (1975), this research proposes an extension of the Theory of Planned Behaviour (TPC) model, with the fundamental objective of evaluating the relationship between leisure time and environmental solid waste recycling behaviour during the COVID-19 pandemic. Through the application of econometric estimations, the results showed that the majority of people who had little free time were more responsible with their waste, compared to those who did not have free time. Therefore, it is affirmed that environmental awareness in Ecuador is not yet fully developed, and it is proposed to reform regulations that encourage people to contribute to the conservation of the environment.